(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and paraclinical characteristics and treatment outcomes of patients with mild acute ischemic stroke at the Emergency Department of Transport Hospital. Methods: A cross-sectional study was conducted on 31 patients aged ≥18 years diagnosed with mild acute ischemic stroke (NIHSS ≤4) admitted within 24 hours of symptom onset and treated at Transport Hospital from July 2023 to October 2024. Data collected included clinical manifestations, laboratory findings, neuroimaging results, TOAST classification, treatment approaches, and discharge status. Data analysis was performed using SPSS 20.0, with statistical significance set at p<0.05. Results: Patients’ ages ranged from 49 to 93 years, with a nearly equal male-to-female ratio (48.4% vs. 51.6%). The most common symptoms were hemiparesis (32.3%), dysarthria (22.6%), and sensory disturbances (19.4%). Hypertension was the predominant risk factor (>75%). Brain lesions were mainly located in the basal ganglia (45.2%), cerebral lobes (25.8%), and subcortical regions (16.1%). Small-vessel disease was the most frequent etiology (48.3%). All patients received conservative medical treatment, with no deaths or referrals reported. Conclusion: Mild acute ischemic stroke has favorable short-term outcomes; however, potential risks of disability and recurrence remain. Early detection, strict vascular risk factor control, and long-term management strategies are essential.